Tingkat pendapatan dan tingkat kepercayaan terhadap kepatuhan wajib pajak - Ariwangsa, I G. N. Oka; Kariyani, Ni Wayan Sri (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
In the life of the state, taxes play a critical role in development. This is because taxes are a source of income. Taxes in this case have an important role in the sustainability of the country, so the active participation of the taxpayer is needed. The aim of this study was to determine the effect of income levels and levels of trust on individual taxpayer compliance at KPP Gianyar. The research method used in this study was a descriptive quantitative research analysis method. The sampling technique used was accidental sampling, and 100 people were obtained. The data source is the primary data from the questionnaire. The data analysis technique is multiple linear regression analysis through the SPSS 26.0 application. The results show that the level of income and the level of trust have a significant positive effect on individual taxpayer compliance.